Музичні жанри: класифікаційні проблеми - Костюк, Н. (Студії мистецтвознавчі, 2007)
Music genres – one of the main terms of the theoretical music studies and music practice, which reflect àesthetic and regulative constants of the music art. The music genres belong to the most important communicative-semantic basics of the artistic systems. This article is an attempt to figure out regulative basics for the development of the music genre theory.